Antimicrobial Susceptibility of Salmonella Isolated from Chickens and Humans in Wau, South Sudan - Saad, Shereen; Jubara, Ambros; Wani, Charles; Munyeme, Musso; Taha, Alfateh; Mudenda, Steward; Zulu, Mildred; Mwasinga, Wizaso; Samutela, Mulemba; Tembo, Rabecca; Muleya, Walter; Kwenda, Geoffrey; et al. (International Journal of Microbiology, 2022)
Background. Salmonella infections are a public health problem across the globe. In South Sudan, there is little information regarding the prevalence and antibiotic resistance patterns of Salmonella. Therefore, this study assessed the prevalence and antimicrobial susceptibility of Salmonella isolates from chickens and humans in South Sudan. Fecal samples were collected and cultured on Xylose Lysine Deoxycholate Agar for the isolation of Salmonella and confirmed using biochemical tests and PCR through the amplification of the invA gene. A total of 417 fecal samples were examined, of which 270 (64.7%) were chicken cloacal swabs while 147 (35.3%) were humans’ stool specimens. Results. Eleven (11) Salmonella isolates were isolated from humans while nine were from chickens. All 11 isolates from humans were susceptible to sulfamethoxazole-trimethoprim, chloramphenicol, streptomycin, cefotaxime, nalidixic acid, and gentamicin. However, 4 (36.7%) isolates showed resistance to ciprofloxacin, 2 (18.9%) to ampicillin, and 1 (9.1%) to tetracycline. All chicken isolates were susceptible to chloramphenicol, streptomycin, sulfamethoxazole-trimethoprim, ciprofloxacin, cefotaxime, nalidixic acid, and gentamicin but showed resistance to tetracycline 2 (22.2%) and ampicillin 1 (11.1%). Conclusion. Antimicrobial resistant isolates were isolated in both chickens and humans. Further, MDR isolates were found in both chicken and human samples, and this is a public health concern. This, therefore, calls for concerted efforts to educate producers and consumers on public health, food safety, food hygiene in food production, and enhancement of surveillance programmes on zoonotic bacteria and antimicrobial susceptibility.